Advanced Oxidation Processes of Amoxicillin Based on Visible Light Active Nitrogen-Doped TiO2 Photocatalyst - Kusuma Putri Suwondo; Nurul Hidayat Aprilita; Endang Tri Wahyuni (Indonesian Journal of Chemistry, 2023)
Environmental consequences during the COVID-19 pandemic have attracted attention due to the excessive use of antibiotics which lead to the release of the drug's residue, such as amoxicillin (AMX), into the environment. In this work, an advanced oxidation process based on a visible, active N-doped TiO2 photocatalyst was carried out to eliminate AMX. Nitrogen with different initial doping concentrations (15, 30, 45% w/w) was doped into TiO2 by the sol-gel method. The characterization technique such as XRD, FTIR, UV-SRS, and SEM-EDX revealed that nitrogen with 30% doping concentration improved the TiO2 response in the visible region, attributed to the lower band gap energy (2.97 eV). In the photodegradation processes, the TiO2-N (30%) photocatalyst possessed higher AMX degradation than undoped TiO2 for both UV and visible light irradiation. In an aqueous solution, the degradation percentage of AMX by TiO2-N (30%) was 68.5 and 84.12%, while the degradation percentage of AMX by TiO2 was 38.7 and 78.01% under visible and UV light, respectively.